Evaluation of Natural Extracts in Animal Models of Pain and Inflammation for a Potential Therapy of Hemorrhoidal Disease - Dragos Paul Mihai; Oana Cristina Seremet; Georgiana Nitulescu; Maria Ivopol; Ani-Simona Sevastre; Simona Negres; Gabriel Ivopol; George Mihai Nitulescu; Octavian Tudorel Olaru (MDPI AG, 2019)
The aim of this work was to assess the analgesic effect of three Vitis vinifera L. leaf extracts and the anti-inflammatory effect of three gels obtained from Aesculus hippocastanum L. seed extracts using animal models, as a preliminary study for the future development of topical preparations based on the combination of extracts with synergistic therapeutic effects on hemorrhoid disease. The analgesic effect was determined by means of the writhing test in mice. The anti-inflammatory effect was determined after administration of carrageenan or kaolin in the rat paw. Extraction using glycerol yielded the highest amounts of flavonoids for both V. vinifera leaves (37.27 ± 1.174 mg/L) and A. hippocastanum seeds (53.48 ± 0.212 mg/L). The highest total phenolic contents were registered for the V. vinifera 20% ethanolic extract (615.3 ± 34.44 mg/L) and for the A. hippocastanum glycerolic extract (247.8 ± 6.991 mg/L). The writhing test revealed that the V. vinifera ethanolic extract induced the most efficient analgesia (57.20%, p < 0.01), better than that induced by the positive control. In the carrageenan inflammation model, only the gel obtained from the A. hippocastanum glycerolic extract significantly reduced paw edema (17.27%, p < 0.05). An anti-inflammatory effect was also observed in the kaolin inflammation model but was not statistically significant (10.12%, p > 0.05). Our findings indicate that V. vinifera and A. hippocastanum extracts may have potential uses for the treatment of pain and inflammation associated with hemorrhoid disease.